The evolution of the panmiction population taking into account destruction of the foetus - Skakauskas, V. (Mathematical Modelling and Analysis, 1996)
“The evolution of the panmiction population taking into account destruction of the foetus”Mathematical Modelling Analysis, 1(1), p. 67-75.First Published Online: 14 Oct 2010